2020
DOI: 10.1107/s2056989020006544
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the one-dimensional coordination polymer formed by the macrocyclic [Ni(cyclam)]2+cation and the dianion of diphenylsilanediylbis(4-benzoic acid)

Abstract: The asymmetric unit of the title compound, catena-poly[[[(1,4,8,11-tetraazacyclotetradecane-κ4 N 1,N 4,N 8,N 11)nickel(II)]-μ-4,4′-(diphenylsilanediyl)dibenzoato-κ2 O:O′] sesquihydrate], {[Ni(C26H18O4Si)(C10H24N4)]·1.5H2O} n , consists of the halves of the centrosymmetric macrocyclic cation and the C 2-symmetric dicarboxylate dianion and of the wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, highly ordered, crystalline polymeric covalent structures, where siloxane motifs alternate with coordinated metal blocks, were obtained with carboxylic ligands, 1,3-bis(carboxypropyl)tetramethyldisiloxane (H 2 CX) prepared for the first time in 1999 [ 15 ], bis(p-carboxyphenyl)diphenylsilane (H 2 L 1 ), and bis(3,4-dicarboxyphenyl)dimethylsilane (H 4 L 2 ) were prepared later [ 126 ] ( Figure 9 a). They were used alone to directly coordinate the metal ions [ 127 , 128 , 129 ] or complexes of the latter with vacancies [ 55 , 99 , 130 , 131 ] or in combination with ancillary organic ligands (imidazole [ 132 , 133 ], 4,4′-bipyridyl [ 134 ], 4,4′-azopyridine [ 56 , 132 , 135 ], 1,2-di(4-pyridyl)ethylene [ 134 ], 1,10-phenanthroline [ 126 ], etc.) ( Figure 9 b) and metal ions or clusters, which allow highly directional intermolecular interactions (metal-ligand, hydrogen bonds and π-π stacking interactions).…”
Section: Highly Ordered Coordination Polymers Containing Silicon or Silicone Motifmentioning
confidence: 99%
See 2 more Smart Citations
“…However, highly ordered, crystalline polymeric covalent structures, where siloxane motifs alternate with coordinated metal blocks, were obtained with carboxylic ligands, 1,3-bis(carboxypropyl)tetramethyldisiloxane (H 2 CX) prepared for the first time in 1999 [ 15 ], bis(p-carboxyphenyl)diphenylsilane (H 2 L 1 ), and bis(3,4-dicarboxyphenyl)dimethylsilane (H 4 L 2 ) were prepared later [ 126 ] ( Figure 9 a). They were used alone to directly coordinate the metal ions [ 127 , 128 , 129 ] or complexes of the latter with vacancies [ 55 , 99 , 130 , 131 ] or in combination with ancillary organic ligands (imidazole [ 132 , 133 ], 4,4′-bipyridyl [ 134 ], 4,4′-azopyridine [ 56 , 132 , 135 ], 1,2-di(4-pyridyl)ethylene [ 134 ], 1,10-phenanthroline [ 126 ], etc.) ( Figure 9 b) and metal ions or clusters, which allow highly directional intermolecular interactions (metal-ligand, hydrogen bonds and π-π stacking interactions).…”
Section: Highly Ordered Coordination Polymers Containing Silicon or Silicone Motifmentioning
confidence: 99%
“…The flexibility of this segment allows the adoption of both cis - [ 133 , 135 ], and trans -oide [ 55 , 133 , 135 ] conformations, in dependence on the coordination geometry of the secondary building units (SBUs) and H-bonding configuration. It was observed that while the complexation of metals with silicone ligands almost always leads to 1D structures [ 55 , 99 , 128 , 131 , 132 , 134 ], in the presence of an organic co-ligand 2D structures are often formed [ 56 , 127 , 132 , 133 , 134 , 135 ]. The 2D structures built with the H 2 Cx ligand are of interest from the perspective of 2D materials, presenting as hydrophobic nano-sheets with very weak interactions between them [ 56 ].…”
Section: Highly Ordered Coordination Polymers Containing Silicon or Silicone Motifmentioning
confidence: 99%
See 1 more Smart Citation
“…Topological analogs exhibit similar connectivity patterns with variations in ligands or metal ions. Structural analogs display similar overall structures with differences in ligand or metal ion arrangements [ [26] , [27] , [28] ].…”
Section: Introductionmentioning
confidence: 99%